FORMULASI KEBIJAKAN PENGGABUNGAN KELURAHAN DI KOTA PAYAKUMBUH PROVINSI SUMATERA BARAT: PELAJARAN MASA LALU DAN ARAH MASA DEPAN - Citra Firmadhani (PRODI ADMINISTRASI PEMERINTAHAN DAERAH FAKULTAS MANAJEMEN PEMERINTAHAN IPDN, 2020)
To date, the target of merging 34 sub-districts of the Payakumbuh Municipal Government has not been achieved, where the Payakumbuh City Government has only succeeded in merging from 76 into 62 villages. Why is the target of merging urban villages in Payakumbuh not being achieved? The author argues that at the level of policy formulation the merger of kelurahan in Payakumbuh City is a crucial factor in not achieving the plan for merging kelurahan. This article seeks to analyze in depth how the policy formulation in the past is then used as a lesson to determine future directions to achieve an effective policy formulation for merging kelurahan in Payakumbuh. To do so, this article seeks to answer three main problems, namely how the effectiveness of the policy formulation for merging urban villages in Payakumbuh City in facilitating the implementation of regional regulations on merging urban villages, what factors hinder the implementation of the policy formulation activities for merging urban villages in Payakumbuh City, and what will be done to overcome obstacles in implementing the policy formulation for merging urban villages in Payakumbuh City. Using qualitative methods, this article ϔinds that the policy formulation has not been effective. Inhibiting factors in this context are the lack of common perceptions between the government and the community, the absence of an agreement on the naming of the new kelurahan, and socialization activities that have not touched the community as a whole. Efforts made to overcome these inhibiting factors were involving community leaders in socialization activities, the government did not intervene at all and left it entirely to the community regarding the naming of new kelurahan, and the government made promises to carry out physical development, such as building roads and bridges. Keywords: Local Government Administration, Merging Kelurahan, Local Autonomy